Analisis Kebutuhan Armada Bus Dalam Trayek dan Waktu Tunggu Pada Terminal Kedatangan di Bandara Internasional Soekarno-Hatta Berdasarkan Headway dan Waktu Sirkulasi - Veronica, Veronica; S, Abdullah Ade Suryobuwono; Hardini, Alifia (Jurnal Sistem Transportasi & Logistik, 2024)
Soekarno-Hatta International Airport is the airport with the most passengers and continues to increase every year. This will certainly affect the airport bus service. Therefore, this study was conducted to determine the transportation needs of the Soekarno-Hatta Airport bus fleet. In this study, the forecasting method was used to see the increase in passengers in the coming year, and the method of calculating fleet needs based on Headway and circulation time, as well as the method of calculating passenger waiting time using actual arrival time and scheduled arrival time. The results of the forecasting show that passengers in 2024 are 26,407,749 and the number of passengers in 2025 is 26,899,319 passengers. The average results of bus arrivals from 26 routes obtained an average of 3 actual arrival schedules that exceeded the standard waiting time for public transportation. Therefore, in overcoming the increase in passengers, there must be an increase in airport infrastructure and the Ottobus company must minimize the factors that affect bus delays.